2001
DOI: 10.1136/heart.85.6.655
|View full text |Cite
|
Sign up to set email alerts
|

Impact of hypertension on the accuracy of exercise stress myocardial perfusion imaging for the diagnosis of coronary artery disease

Abstract: Aim-To compare the accuracy of exercise stress myocardial perfusion single photon emission computed tomography (SPECT) imaging for the diagnosis of coronary artery disease in patients with and without hypertension. Methods-A symptom limited bicycle exercise stress test in conjunction with 99m technetium sestamibi or tetrofosmin SPECT imaging was performed in 332 patients (mean (SD) age, 57 (10) years; 257 men, 75 women) without previous myocardial infarction who underwent coronary angiography. Of these, 137 (4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 27 publications
1
12
1
1
Order By: Relevance
“…In fact, in accordance with the results obtained in the present study, perfusion abnormalities have been described in asymptomatic patients with systemic hypertension (30). The accuracy of myocardial perfusion scintigraphy in the detection of significant coronary artery disease has been reported to be in the range of 85-98% (31), but the issue of whether abnormal scan findings represent true perfusion changes or may be interpreted as false-positive remains controversial in nuclear cardiology.…”
Section: Discussionsupporting
confidence: 89%
“…In fact, in accordance with the results obtained in the present study, perfusion abnormalities have been described in asymptomatic patients with systemic hypertension (30). The accuracy of myocardial perfusion scintigraphy in the detection of significant coronary artery disease has been reported to be in the range of 85-98% (31), but the issue of whether abnormal scan findings represent true perfusion changes or may be interpreted as false-positive remains controversial in nuclear cardiology.…”
Section: Discussionsupporting
confidence: 89%
“…In these patients, stress nuclear techniques have similar diagnostic sensitivity and specificity to those observed in patients without LVH. The diagnostic value of myocardial perfusion SPECT is not generally degraded by the presence of hypertension without evidence of LVH, 33 although an increased frequency of false-positive studies has been reported in athletes. 34 Similarly, although the number of reports is small, the prognostic value of myocardial perfusion SPECT in patients with LVH appears to be equal to that observed in patients without LVH.…”
Section: Left Ventricular Hypertrophymentioning
confidence: 99%
“…Both left ventricular hypertrophy (more than 75% of our study population had a history of hypertension) and microvascular disease may be associated with perfusion abnormalities in the presence of normal coronary arteries (21,30,31). The precise impact of these confounders remains unknown; however, hypertension does not degrade the diagnostic value of MPS for diagnosing coronary artery disease (32), and none of the factors can explain the high rate of insignificant angiographic disease in these patients. Also possible are differences in practice and assessment of symptoms.…”
Section: Discussionmentioning
confidence: 99%